Ekspedisjonsfotografi i polare områder - Barr, Susan (Bildet lever! : bidrag til norsk fotohistorie. 7, 1999)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

Roald Amundsen conquers the South Pole - Berg, Kåre (Norwegian maritime explorers and expeditions : over the past thousand years, 1999)
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; oppdagelsesreiser

The importance of charged aerosols in the polar mesosphere in connection with Noctilucent Clouds and Polar Mesosphere Summer Echoes - Blix, Tom Arild (The Antarctic and Arctic Middle Atmospheres: Their Differences and Similarities, 1999)
A number of campaigns have been conducted in order to study Polar Mesosphere Summer Echos (PMSE) and Noctilucent Clouds (NLC) in the period 1991–1994. Several sounding rockets have been launched through these layers with measurements being performed on upleg as well as downleg. These include measurements of positive ions and electrons in both ram and wake positions, as well as measurements of charged aerosols in ram on upleg. In this paper we will review these measurements and make a preliminary classification of the data based upon the presence of PMSE and/or NLC. One of the mechanisms responsible for PMSE is the presence of neutral air turbulence in combination with a high Schmidt number. We will briefly discuss this type of echo using in situ rocket data. Differences and similarities of PMSE and NLC as observed both in the Arctic and the Antarctic will be discussed. Observations show that especially PMSE are much more frequent in the Arctic. This may be due to a difference in the water vapour content or the temperature at mesopause heights. Lack of data in the Antarctic makes it difficult to decide which of these two factors are the most important. More measurements, especially co-ordinated in situ and ground-based lidar and radar measurements, are needed to discuss the Arctic and Antarctic similarities and differences in further detail.
Keywords: Antarktis; astrofysikk; atmosfæren; geofysikk; mesosfæren; meteorologi; polarområdene

C.A. Larsen - Pioneer of the Antarctic ocean - Devig, Thor N (Norwegian maritime explorers and expeditions : over the past thousand years, 1999)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangst; kartlegging; oppdagelsesreiser; pelagisk; polarekspedisjoner

Søylegangen i Buenos Aires - Fløgstad, Kjartan (Eld og vatn : nordmenn i Sør-Amerika, 1999)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Roald Amundsen; hvalfangere; hvalfangstindustri; oppdagelsesreiser; pelagisk

The cryosphere: an early indicator and global player - Grassl, Hartmut (Polar Research, 1999)
Ice at or below the surface of the planet Earth is an important part of the climate system. The solid phase of water has two unique characteristics which make it both an early indicator of climate change and a global player. First, if warmed to the melting point at 0°C, higher air temperatures and/or higher long-wave back radiation just increase the melting rate but not - as with all other surfaces- the temperature, which stays at 0°C. Small icecaps and mountain glaciers thus become early indicators of a changed climate. Second. If seawater is cooled to the freezing point at about- 1.8"C. the sea ice formation process ejects salt causing the denser water to sink, thereby filling the global ocean interior with very cold water. The location where most of this deep convection occurs is strongly dependent on the freshwater balance and thus on the average salinity of ocean basins. Present ocean configuration and ocean topography, as well as precipitation distribution, make the northern North Atlantic more saline than any other high latitude ocean part and thus the site with most of this deep water formation. Sea ice formation is therefore of high significance for the European climate. Since it drives the near surface warm North Atlantic current northward off the European coast in compensation for southward deep water flow in the western Atlantic, northwestern Europe is warmer by about 4°C than the same latitudes on the eastern Pacific coast of America.
Keywords: Antarktis; isbreer; klimaendringer; kryosfæren; polarområdene; sjøvann; vann

Predicted present-day evolution patterns of ice thickness and bedrock elevation over Greenland and Antarctica - Huybrechts, Philippe; Le Meur, Emmanuel (Polar Research, 1999)
This paper discusses predicted evolution patterns of present-day changes of ice thickness, surface elevation, and bedrock elevation over the Greenland and Antarctic continents. These were obtained from calculations with dynamic 3-D ice sheet models which were coupled to a visco-elastic solid Earth model. The experiments were initialized over the last two glacial cycles and subsequently averaged over the last 200 years to obtain the current evolution. The calculations indicate that the Antarctic Ice Sheet is still adjusting to the last glacial-interglacial transition yielding a decreasing ice volume and a rising bedrock elevation of the order of several centimetres per year. The Greenland Ice Sheet was found to be close to a stationary state with a mean thickness change of only a few millimetres per year, but the calculations revealed large spatial differences. Predicted patterns over Greenland are characterized by a small thickening over the ice sheet interior and a general thinning of the ablation area. In Antarctica, almost all of the predicted changes are concentrated in the West Antarctic Ice Sheet, which is still retreating at both the Weddell and Ross Sea margins. Over most of both ice sheets, the model indicates that the surface elevation trend is dominated by ice thickness changes rather than by bedrock elevation changes.
Keywords: Antarktis; glasiologi; innlandsis; polarområdene

The Antarctic contribution to Holocene global sea level rise - Ingólfsson, Ólafur; Hjort, Christian (Polar Research, 1999)
The Holocene glacial and climatic development in Antarctica differed considerably from that in the Northern Hemisphere. Initial deglaciation of inner shelf and adjacent land areas in Antarctica dates back to between 10-8 Kya, when most Northern Hemisphere ice sheets had already disappeared or diminished considerably. The continued deglaciation of currently ice-free land in Antarctica occurred gradually between ca. 8-5 Kya. A large southern portion of the marine-based Ross Ice Sheet disintegrated during this late deglaciation phase. Some currently ice-free areas were deglaciated as late as 3 Kya. Between 8-5 Kya, global glacio-eustatically driven sea level rose by 10-17m, with 4-8 m of this increase occurring after 7 Kya. Since the Northern Hemisphere ice sheets had practically disappeared by 8-7 Kya, we suggest that Antarctic deglaciation caused a considerable part of the global sea level rise between 8-7 Kya, and most of it between 7-5 Kya. The global mid-Holocene sea level high stand, broadly dated to between 8-4 Kya, and the Littorina-Tapes transgressions in Scandinavia and simultaneous transgressions recorded from sites e.g. in Svalbard and Greenland, dated to 7-5 Kya, probably reflect input of meltwater from the Antarctic deglaciation.
Keywords: Antarktis; geologi; glasiologi; havnivåstigning; innlandsis; paleoglasiologi; polarområdene

Ultraviolet radiation and health effects in the Antarctic - Lugg, Desmond J.; Roy, Colin R. (Polar Research, 1999)
With the recognition that global climate change may adversely affect human health, there has been an increase in relevant research worldwide. In the Antarctic medical research has been largely directed at the potential health effects of stratospheric ozone depletion. For over a decade continuous broad-band measurements of ultraviolet radiation (UVR) have been made at all Australian stations. Results of UV measurements are presented and comparisons made with the “ozone hole” moving over the stations, erythemal UVR increasing by a factor of more than 2.5 over a three day period. During late spring and despite the large difference in latitude, Davis, Antarctica, and Melbourne, Australia, are very similar in erythemal UVR. Antarctic immunological and photo biological research is presented and the role of UVR discussed. Epidemiological data is reviewed for short-term links between UVR and related disease. With increased awareness of the dangers of UVR and consequent changes in sun-related behavior, the incidence of the acute effects of UVR is much lower than decades ago. As the itinerant Antarctic population spends a maximum of 12-18 months at a time in that location it is an excellent control group for studies on the health effects of UVR on permanent populations at similar latitudes in the Arctic.
Keywords: Antarktis; epidemiologi; fotobiologi; immunologi; klimaendringer; ozonlaget; ultrafiolett stråling

Photosynthetic responses of selected Antarctic plants to solar radiation in the southern maritime Antarctic - Montiel, Pedro; Smith, Andrew; Keiller, Don (Polar Research, 1999)
The effects of UV-B exclusion and enhancement of solar radiation on photosynthesis of the two phanerogams which occur in the maritime Antarctic, Deschampsia antarctica and Colobanthus quitensis, and the moss Sanionia uncinats were investigated. Data on air temperature and solar radiation illustrate a drastic seasonal variation. Daily O3 column mean values and UV-B measured at ground level document the occurrence of the O3“hole” in the spring of 1997, with a concomitant increase in UV-B. The grass, D. antarctica, exhibited a broad temperature optimum for photosynthesis between 10–25°C while photosynthesis did not saturate even at high irradiance. The high water use efficiencies measured in the grass may be one of the features explaining the presence of this species in the maritime Antarctic. The net photosynthesis response to intercellular CO2 (A/ci) for D. antarctica was typical of a C3 plant. Exposure to a biologically effective UV-B irradiance of 0.74 W M-2 did not result in any significant change in either the maximum rate of photosynthesis at saturating CO2 and light, or in the initial carboxylation efficiency of Rubisco. (Vc,max). Furthermore while ambient (or enhanced) solar UV-B did not affect photochemical yield, measured in the field, of C. quitensis and D. antarctica, UV-B enhancement did affect negatively photochemical yield in S. uncinata. In D. antarctica plants, exposure to UV-B at low irradiances elicited increased flavonoid synthesis. The observed effects of UV-B enhancement on the moss (decreased photochemical yield) and the grass (increase in flavonoids) require further, separate investigation.
Keywords: Antarktis; botanikk; fotosyntese; klimaendringer; moser; planter

Antarktis : norsk natur- og kulturminneforvaltning - Njåstad, Birgit (ed.) (Norsk Polarinstitutt, 1999)
Keywords: Antarktis; Norge; forvaltning; kulturminneforvaltning; miljøvern; naturforvaltning; naturvern; polarområdene

Global change and the polar regions - Rapley, Chris (Polar Research, 1999)
Keywords: Antarktis; klimaendringer; polarområdene

A study of the ice dynamics of Jutulstraumen drainage area, by means of remote sensing - Rolstad, Cecilie; Hagen, Jon Ove; Østen, Kristoffer; Tonning, Tore; Semb, Svein Ingar (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Antarktis; NARE 1997/98; akkumulasjon; glasiologi; innlandsis; klimaendringer

A global model tool for three-dimensional multiyear stratospheric chemistry simulations: Model description and first results - Rummukainen, Markku; Isaksen, Ivar S A; Rognerud, Bjørg; Stordal, Frode (Journal of Geophysical Research: Atmospheres, 1999)
The paper presents a new global modeling tool, Stratospheric Chemical Transport Model 2. It has been developed for effective three-dimensional multiyear stratospheric chemistry studies, featuring an extensive chemistry scheme, heterogeneous processing on sulfate aerosols, and some polar stratospheric cloud processes. The transport algorithm maintains sub-grid-scale distributions and connects vertically the stratospheric layers, even in a coarse vertical grid. The model has been integrated for 49 months, recycling 1 year of precalculated transport from a middle atmosphere general circulation model. One year of daily National Centers for Environmental Prediction global analyses are used as temperatures. Diurnal cycles of photolysis rates are recalculated every 7 days to give interaction with ozone changes. The model is able to describe most of the geographical and seasonal ozone variability and the meridional distributions of ozone, reactive nitrogen, chlorine, and bromine. Stratospheric diurnal cycles for nitrogen, hydrogen, chlorine, and bromine species are captured in detail. The upper stratosphere ozone deficiency, typical to models, is large. Its sensitivity to different ways of tuning are explored. Midlatitude, rather than polar, wintertime processes have so far been the focus in this model tool. The present transport and grid resolution are not suited for realistic simulations at high latitudes. As there is only a limited inclusion of polar stratospheric cloud (PSC) microphysics, chemical processing in the cold polar lower stratosphere also cannot be well simulated. For example, the Antarctic ozone hole is not simulated, but the modeled chemistry should be suitable for warm Arctic winters when type II PSCs and particle sedimentation do not occur.
Keywords: Antarktis; geofysikk; meteorologi; ozonlaget; polarområdene; stratosfæren; stratosfærisk kjemi

Climatic trend and the retreat and disintegration of ice shelves on the Antarctic Peninsula: an overview - Skvarca, Pedro; Rack, Wolfgang; Rott, Helmut; Ibarzábal Donángelo, Teresa (Polar Research, 1999)
Observation of the retreat and disintegration of ice shelves around the Antarctic Peninsula during the last three decades and associated changes in air temperature, measured at various meteorological stations on the Antarctic Peninsula, are reviewed. The climatically induced retreat of the northern Larsen Ice Shelf on the east coast and of the Wordie, George VI, and Wilkins ice shelves on the west coast amounted to about 10 000 km2 since the mid-1960s. A summary is presented on the recession history of the Larsen Ice Shelf and on the collapse of those sections north of Robertson Island in early 1995. The area changes were derived from images of various satellites, dating back to a late 1963 image from the recently declassified US Argon space missions. This photograph reveals a previously unknown, minor advance of the northern Larsen Ice Shelf before 1975. During the period of retreat a consistent and pronounced warming trend was observed at the stations on both east and west coasts of the Antarctic Peninsula, but a major cause of the fast retreat and final collapse of the northernmost sections of the Larsen Ice Shelf were several unusually warm summers. Temperature records from the nearby station Marambio show that a positive mean summer temperature was reached for the first time in 1992-93. Recent observations indicate that the process of ice shelf disintegration is proceeding further south on both sides of the Antarctic Peninsula.
Keywords: Antarktis; brehylle; glasiologi; isbrem; isshelf; klimaendringer; meteorologi; satellittbilder

Report of the Norwegian Antarctic Research Expedition 1997/98 - Tveraa, Torkild (ed.); Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1999)
Keywords: Antarktis; NARE 1997/98; biologi; geodesi; glasiologi; oseanografi

Distribution and Abundance of the Antarctic Petrel - van Franeker, J. A.; Gavrilo, M.; Mehlum, Fridtjof; Veit, R. R.; Woehler, E. J. (Waterbirds: The International Journal of Waterbird Biology, 1999)
Published and unpublished information on the distribution and abundance of the Antarctic Petrel (Thalassoica antarctica) is reviewed. Currently 35 colonies with approximately half a million breeding pairs are known. All but one of these known colonies are situated in East Antarctica. However, an estimate derived from at sea studies in three of four apparent centers of oceanic occurrence suggests a population as high as four to seven million breeding pairs (10 to 20 million individuals). In spite of the tentative nature of such an estimate, the difference with the colony-derived figure strongly suggests the existence of large, currently undiscovered colonies, particularly in western Antarctica and Victoria Land, where a complete mismatch exists between bird observations at sea and known colonies. In eastern Antarctica, in addition to undiscovered colonies, some known ones could be considerably larger than currently documented.
Keywords: Antarktis; Dronning Maud Land; fugler; ornitologi; petreller; zoologi

The interplay of global and polar regimes - Young, Oran R. (Polar Research, 1999)
The growing salience of interactions between the functionally broad but geographically narrow regimes for the polar regions and the geographically broad but functionally specific regimes emerging to deal with global environmental changes directs attention to the issue of institutional interplay. Interplay among regimes can cause mutual interference or foster synergy. Adopting a pragmatic stance that assumes no fundamental changes in international society, this essay suggests ways to: (1) adapt global regimes dealing with ozone depletion, climate change and biodiversity to the conditions prevailing in the polar regions; and (2) ensure that concerns arising in the polar regions receive serious consideration in global forums. Specific suggestions range from modest initiatives involving monitoring and assessment to more ambitious initiatives, such as the establishment of a chamber of regions in global regimes.
Keywords: Antarktis; biodiversitet; internasjonal samarbeid; klimaendringer; klimapolitikk; ozonlaget; polarområdene

Dagboken fra Belgica-ekspedisjonen 1897-99 : Roald Amundsens første ferd til Antarktis - Amundsen, Roald (Vågemot miniforl., 1998)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; dagbøker; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Ice sheet history from Antarctic Continental Margin sediments: The ANTOSTRAT approach - Barker, Peter; Barrett, Peter; Camerlenghi, Angelo; Cooper, Alan; Davey, Frederick; Domack, Eugene; Escutia, Carlota; Kristoffersen, Yngve; O'Brien, Philip (Terra Antarctica, 1998)
Keywords: Antarktis; glasiologi; innlandsis; sedimentologi

“Convergence or National Styles? The Japanese Challenge to the British-Norwegian Hegemony in the Twentieth-Century Whaling Industry” - Basberg, Bjørn L (Global Markets: The Internationalization of the Sea Transport Industries since 1850, 1998)
Keywords: Antarktis; Svend Foyn; fiskeindustri; hvalfangst; hvalfangstindustri; hvalfangstnæring; hvalindustri; pelagisk; økonomi

Roald Amundsen : en biografi - Bomann-Larsen, Tor (Cappelen, 1998)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolen; biografi; ekspedisjoner; oppdagelsesreiser

On the cost of reproduction in long-lived birds: the influence of environmental variability - Erikstad, Kjell Einar; Fauchald, Per; Tveraa, Torkild; Steen, Harald (Ecology, 1998)
Keywords: Antarktis; fugler; ornitologi; petreller; zoologi

Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norge og polarområdene - Hansson, Rasmus (ed.) (Utenriksdepartementet, 1998)
Keywords: Antarktis; Norge; geografi; historie; miljøvern; polarforskning; polarområdene; politikk

Ambient air levels and atmospheric long-range transport of persistent organochlorines to Signy Island, Antarctica - Kallenborn, Roland; Oehme, Michael; Wynn-Williams, David D; Schlabach, Martin; Harris, Joyce (Science of The Total Environment, 1998)
Levels of persistent organic pollutants (POPs), such as polychlorinated biphenyls and pesticides have been determined in ambient air at Signy Island, Antarctica, over a period of 17 weeks. Mean concentrations for single polychlorinated biphenyls (0.02–17 pg/m3), for chlordanes (0.04–0.9 pg/m3), DDT compounds (0.07–0.40 pg/m3) and γ-hexachlorocyclohexane (HCH, 22 pg/m3) were comparable to those in Arctic air. However, α-HCH levels were approximately one order of magnitude lower. Compared to the Arctic, differences were also observed in the concentration ratios of α-/γ-HCH and chlordane compounds. Two possible atmospheric long-range transport episodes from South America were found by comparing 10-day back trajectories with observed concentration changes. The lower limits of determination (LOD) were mainly governed by the field blanks. They were satisfactory for the most volatile PCBs. However, many concentrations for DDT and chlordane compounds were below the LODs (range 0.1–1 pg/m3) or even the instrumental detection limit (0.01–0.03 pg/m3).
Keywords: Antarktis; atmosfæren; forurensning; langtransport; luftforurensning; meteorologi; miljøgifter; polarområdene

Antarctic Protected Areas Workshop : workshop report - Njåstad, Birgit (ed.) (Norsk Polarinstitutt, 1998)
Keywords: Antarktis; kongress; miljøvern; naturvern

Klarius Mikkelsen's 1935 landing in the Vestfold Hills, East Antarctica: some fiction and some facts - Norman, Frederick Ian; Gibson, John A E; Burgess, J S (Polar Record, 1998)
Exploratory activities of Norwegians, particularly those directed by Lars Christensen, off eastern Antarctica are discussed briefly in relation to contemporary Antarctic investigations and politics. The interests of Norway there and Christensen's role in establishing an understanding of the local coastline are indicated. Particular attention is paid to the landing made by Klarius Mikkelsen in the Vestfold Hills, East Antarctica, on 20 February 1935. Note is taken of the site's recent re-discovery, and the symbolic role of the landing in the national aspirations of Norway, Britain, and Australia is discussed. Mikkelsen operated under commercial and scientific interests promoted by Christensen, and his landing was, at least in published material, seen as an extension of them. However, there is a suggestion that not only had a new Norwegian land been discovered, and a landing made, but that a claim to it was at least considered. Such a claim was not appropriate given previous agreements between Norway and Britain. The site's location and environs are discussed, as are subsequent flights over it and visits made there by Australian expeditioners. The ambiguity associated with claims that Caroline Mikkelsen was the first woman to land on the Antarctic mainland is also examined. Since Mikkelsen's site was on an island within the Tryne Group, to the north of Davis station, if a mainland location is required to establish such an event, then an alternative (Scullin Monolith) is proposed; however, on this occasion four women were involved, but who was first ashore remains uncertain.
Keywords: Antarktis; Nordmenn; Thorshavn ekspedisjon; første landgang; kvinner; oppdagelsesreiser

A new species of Parmelia (lichenized Ascomycotina) from the Antarctic - Øvstedal, Dag Olav; Elix, John A.; Smith, Ronald I. Lewis (Mycotaxon, 1998)
A new species of Parmelia (lichenized Ascomycotina) from the Antarctic. Parmelia lindsayana Ovstedal & Elix from Signy Island (South Orkney Islands) is described as new. This species resembles P. protosulcata Hale and P. cunninghamii Crombie, but differs in morphological details and in containing usnic, alpha-collatolic and alectoronic acids.
Keywords: Antarktis; Sør-Orknøyene; botanikk; lav; planter

A Comparison of the CCM3 Model Climate Using Diagnosed and Predicted Condensate Parameterizations - Rasch, Philip J.; Kristjánsson, Jón Egill (Journal of Climate, 1998)
A parameterization is introduced for the prediction of cloud water in the National Center for Atmospheric Research Community Climate Model version 3 (CCM3). The new parameterization makes a much closer connection between the meteorological processes that determine condensate formation and the condensate amount. The parameterization removes some constraints from the simulation by allowing a substantially wider range of variation in condensate amount than in the standard CCM3 and tying the condensate amount to local physical processes. The parameterization also allows cloud drops to form prior to the onset of grid-box saturation and can require a significant length of time to convert condensate to a precipitable form, or to remove the condensate. The free parameters of the scheme were adjusted to provide reasonable agreement with top of atmosphere and surface fluxes of energy. The parameterization was evaluated by a comparison with satellite and in situ measures of liquid and ice cloud amounts. The effect of the parameterization on the model simulation was then examined by comparing long model simulations to a similar run with the standard CCM and through comparison with climatologies based upon meteorological observations. Global ice and liquid water burdens are higher in the revised model than in the control simulation, with an accompanying increase in height of the center of mass of cloud water. Zonal averages of cloud water contents were 20%–50% lower near the surface and much higher above. The range of variation of cloud water contents is much broader in the new parameterization but was still not as large as measurements suggest. Differences in the simulation were generally small. The largest significant changes found to the simulation were seen in polar regions (winter in the Arctic and all seasons in the Antarctic). The new parameterization significantly changes the Northern Hemisphere winter distribution of cloud water and improves the simulation of temperature and cloud amount there. Small changes were introduced in the cloud fraction to improve consistency of the meteorological parameterizations and to attempt to alleviate problems in the model (in particular, in the marine stratocumulus regime). The small changes did not make any appreciable improvement to the model simulation. The new parameterization adds significantly to the flexibility in the model and the scope of problems that can be addressed. Such a scheme is needed for a reasonable treatment of scavenging of atmospheric trace constituents, and cloud aqueous or surface chemistry. The addition of a more realistic condensate parameterization provides opportunities for a closer connection between radiative properties of the clouds, and their formation and dissipation. These processes must be treated for many problems of interest today (e.g., anthropogenic aerosol–climate interactions).
Keywords: Antarktis; klimamodeller; klimatologi; meteorologi; polarområdene

Sydpolen - Skattum, Ole Jacob (Roald Amundsen som geografisk oppdager, 1998)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

Caloplaca Lewis-Smithii, a new lichen species from continental Antarctica - Søchting, Ulrik; Øvstedal, Dag Olav (Mycotaxon, 1998)
A new muscicolous lichen species, Caloplaca lewis-smithii Søchting & Øvst., is described from Victoria Land, continental Antarctica. It is characterized by a grey to blackish brown microlobate thallus and a blackish apothecial disk with a white pruinose thalline margin.
Keywords: Antarktis; botanikk; lav; planter; sopper

The semi-annual oscillation and Antarctic climate. Part 1: influence on near surface temperatures (1957–79) - Van Den Broeke, Michiel R. (Antarctic Science, 1998)
We studied the influence of the semi-annual oscillation (SAO) on near-surface temperatures in Antarctica, using observations of 27 stations that were operational during (part of) the period 1957–79. For the annual cycle of surface pressure, the second harmonic explains 17–36% of the total variance on the Antarctic Plateau, 36–68% along the East Antarctic coast and almost 80% on the west coast of the Peninsula, and decreases further to the north. As a result of the amplification of the wave-3 structure of the circulation around Antarctica, a significant modification of the seasonal cooling is observed at many stations. The magnitude of this modification is largely determined by the strength of the temperature inversion at the surface: the percentage of the variance explained by the second harmonic of the annual temperature cycle is then largest on the Antarctic Plateau (11–18%), followed by the large ice shelves and coastal East Antarctica (6–12%) and stations at or close to the Peninsula (0–5%). A significant coupling between the half-yearly wave in surface pressure and that in surface temperature is found for coastal East Antarctica, which can be directly explained by the changes in meridional circulation brought about by the SAO. We show that the coupling of Antarctic temperatures to the meridional circulation is not only valid on the seasonal time scale of the SAO, but probably also on daily and interannual time scales. This has important implications for the interpretation of time series of Antarctic temperatures, a problem that will be addressed in part 2 of this paper.
Keywords: Antarktis; fysisk geografi; klimatologi; meteorologi

The semi-annual oscillation and Antarctic climate. Part 2: recent changes - Van Den Broeke, Michiel R. (Antarctic Science, 1998)
Following a weakening of the semi-annual oscillation (SAO) since the mid-1970s, the half-yearly pressure wave in the Southern Hemisphere has become less significant. As a result, May/June temperatures have decreased in East Antarctica, which has moderated Antarctic warming. Spectral analysis of 87 years of pressure data at Orcadas suggest that the recent weakening of the SAO is part of the natural variability of the Southern Hemisphere circulation on decadal timescales. We interpret the time series of composite Antarctic temperature in terms of the historical strengthening and weakening of the SAO. If the dominant oscillations that occurred in the past prove to be persistent, an accelerated East Antarctic warming trend is expected for the coming decades. There are indications that the strength of the SAO is linked to the Southern Oscillation, in the sense that warm phases of the Southern Oscillation coincide with strong westerlies, a weakly developed SAO and below-average temperatures in East Antarctica. Temperatures on the west coast of the Antarctic Peninsula show strongly deviant patterns, which can not be explained by the same mechanism that applies to East Antarctica.
Keywords: Antarktis; fysisk geografi; klimatologi; meteorologi

Validation of Ground-Based Visible Measurements of Total Ozone by Comparison with Dobson and Brewer Spectrophotometers - Van Roozendael, Michel; Peeters, P.; Roscoe, H. K.; De Backer, H.; Jones, A. E.; Bartlett, L.; Vaughan, G.; Goutail, Florence; Pommereau, Jean-Pierre; Kyro, E.; Wahlstrom, C.; Braathen, Geir; et al. (Journal of Atmospheric Chemistry, 1998)
Comparisons of total column ozone measurements from Dobson, Brewer and SAOZ instruments are presented for the period 1990 to 1995 at seven stations covering the mid- and the high northern latitudes, as well as the Antarctic region. The main purpose of these comparisons is to assess, by reference to the well established Dobson network, the accuracy of the zenith-sky visible spectroscopy for the measurement of total ozone. The strengths and present limitations of this latter technique are investigated. As a general result, the different instruments are found to agree within a few percent at all stations, the best agreement being obtained at mid-latitudes. On average, for the mid-latitudes, SAOZ O3 measurements are approximately 2% higher than Dobson ones, with a scatter of about 5%. At higher latitudes, both scatter and systematic deviation tend to increase. In all cases, the relative differences between SAOZ and Dobson or Brewer column ozone are characterised by a significant seasonal signal, the amplitude of which increases from about 2.5% at mid-latitude to a maximum of 7.5% at Faraday, Antarctica. Although it introduces a significant contribution to the seasonality at high latitude, the temperature sensitivity of the O3 absorption coefficients of the Dobson and Brewer instruments is shown to be too small to account for the observed SAOZ/Dobson differences. Except for Faraday, these differences can however be largely reduced if SAOZ AMFs are calculated with realistic climatological profiles of ozone, pressure and temperature. Other sources of uncertainties that might affect the comparison are investigated. Evidence is found that the differences in the air masses sampled by the SAOZ and the other instruments contribute significantly to the scatter, and the impact of the tropospheric clouds on SAOZ measurements is displayed.
Keywords: Antarktis; klimatologi; ozon; polarområdene; spektrofotometri; stratosfæren

Strategy for Norwegian research in Antarctica (The Research Council of Norway, 1997)
Keywords: Antarktis; polarforskning

Productivity in the 20th century Antarctic pelagic shore station whaling: growth and stagnation in two technological regimes. - Basberg, Bjørn L (The Great Circle, 1997)
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalfangststasjoner; hvalindustri; pelagisk

To hvalfangstentreprenøren - to strategier? - Basberg, Bjørn L (I det lange løp : essays i økonomisk historie tilegnet Fritz Hodne, 1997)
Keywords: Antarktis; Carl Anton Larsen; Christen Christensen; Norge; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalfangststasjoner; hvalkokerier; næringsliv; pelagisk; økonomi

Kulturhistorisk forskning i Antarktis - Basberg, Bjørn Lorens (HIFO-nytt : medlemsblad for Norsk historikerforening, 1997)
Keywords: Antarktis; hvalfangst; kulturhistorie; kulturminner

Analysis of merged SMMR-SSMI time series of Arctic and Antarctic sea ice parameters 1978–1995 - Bjørgo, Einar; Johannessen, Ola M.; Miles, Martin W. (Geophysical Research Letters, 1997)
The most consistent means of investigating the global sea ice cover is by satellite passive microwave sensors, as these are independent of illumination and cloud cover. The Nimbus 7 Scanning Multichannel Microwave Radiometer (SMMR) and the Defense Meteorological Satellite Program (DMSP) Special Sensor Microwave Imager (SSMI) provide information on the global sea ice cover from 1978 to present. The two instruments flew simultaneously during a 6-week overlap period in July and August 1987, thus enabling intercomparison of the two sensors. Brightness temperatures are corrected for instrument drift and calibration differences in order to produce continuous time series of monthly averaged Arctic and Antarctic sea ice extent and sea ice area through the use of the NOrwegian Remote Sensing EXperiment (NORSEX) algorithm, which relates brightness temperatures to ice concentration. Statistical analysis on the time series estimates the decreases in Arctic ice extent and ice area to be 4.5% and 5.7%, respectively, during the 16.8-year observation period. The overall trends established here serve to better define and strengthen earlier assertions of a reduced ice cover, based on analysis of SMMR and SSMI data taken separately. These results are consistent with GCM simulations that suggest retreat of the sea ice cover under global warming scenarios.
Keywords: Antarktis; global oppvarming; havis; klimaendringer; meteorologi; polarområdene; satellite mikrobølgesensorer

Representation of Antarctic Katabatic Winds in a High-Resolution GCM and a Note on Their Climate Sensitivity - Broeke, Michiel R. van den; Wal, Roderik S. W. van de; Wild, Martin (Journal of Climate, 1997)
Keywords: Antarktis; Dronning Maud Land; glasiologi; klimatologi; meteorologi

Responses of terrestrial plants and invertebrates to environmental change at high latitudes - Callaghan, Terry V.; Sonesson, Mats; Sømme, Lauritz; Walton, D. W. H.; Christensen, T.; Block, W. C.; Drewry, D. J.; Laws, Richard Maitland; Pyle, John Adrian (Philosophical Transactions of the Royal Society of London. Series B: Biological Sciences, 1997)
Many invertebrates show flexibility in their life cycles and are likely to respond to changes in climate as they have in the past. However, changes in temperature and photoperiod may disturb the life cycles of some existing polar invertebrates while continuing to constrain the polewards migration of more temperate species. Higher plants are likely to have higher productivity as temperatures and atmospheric CO2 levels increase but this productivity will be reduced by exposure to increasing UV-B radiation. Higher plants migrate more slowly than the rate at which climate is predicted to change and many species will be trapped in supra-optimal climates. Both mosses and lichens can migrate faster than higher plants, propagules of non-polar species already reaching the Antarctic, but they have fewer mechanisms of responding to changing environments. Polar vegetation and ecosystems provide feedback to the climate system: positive feedbacks are associated with decreases in reflectivity and increased carbon emissions from warm ing soils. In the Antarctic, feedback and responses to environmental change will be smaller than in the Arctic because of the less responsive cryptogams which dominate the Antarctic, the paucity of Antarctic soils, and geographical barriers to plant and invertebrate migrations.
Keywords: Antarktis; biologi; botanikk; klimaendringer; lav; moser; virvelløse dyr

Et større Norge 1949-65 - Eriksen, Knut Einar (Kald krig og internasjonalisering, 1949-1965, 1997)
Keywords: Antarktis; Norge; historie; internasjonal; polarområdene; politikk; utenrikspolitikk

Antarctic waste management handbook - Kankaanpää, Paula; Njåstad, Birgit; Eriksson, Cecilia (Norwegian Polar Institute, 1997)
Keywords: Antarktis; avfallshåndtering; forskningsstasjoner; miljø

Den tredje mann : beretningen om Hjalmar Johansen - Kvam, Ragnar (Gyldendal, 1997)
Keywords: Antarktis; Nordmenn; Sydpolsekspedisjonen; biografier; oppdagelsesreiser; polarekspedisjoner; polarhistorie

Environmental aspects - NARE 96/97 - Njåstad, Birgit (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Antarktis; Antarktistraktaten; NARE 1996/97; miljøvern

Anatomy and microbiology of the digestive tract of the Adelie penguin - Olsen, Monica Alterskjær; Mathiesen, Svein Disch (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Antarktis; NARE 1996/97; biologi; pingviner; zoologi

Report of the Norwegian Antarctic Research Expedition 1992/93 - Orheim, Olav (ed.) (Norsk Polarinstitutt, 1997)
Keywords: Antarktis; NARE 1992/93; ekspedisjoner; geofysikk; geologi; glasiologi; marin biologi; marin geologi; ornitologi; oseanografi; topografi

Hot water drilling near Filchner station, Ronne ice shelf - Orheim, Olav; Østerhus, Svein; Melvold, Kjetil; Eiken, Trond; Thomsen, Henrik Højmark; Winther, Jan-Gunnar; Bævre, Halvor (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Antarktis; NARE 1992/93; glasiologi; havstrømmer; isshelf; oseanografi; vannmasser

Alene over Antarktis - Ousland, Børge ([B. Ousland], 1997)
Keywords: Antarktis; ekspedisjoner; reiser; reiseskildringer; skiekspedisjoner

Hvalfangstbase og kulturminne, Hektor Hvalfangststasjon : den sørligste av de norske landstasjonene i Antarktis - Rossnes, Gustav (Norsk sjøfartsmuseum. Årsberetning, 1997)
Keywords: Antarktis; Deceptionøya; Norge; fangststasjoner; hvalfangere; hvalfangst; hvalfangststasjoner

Convergent flow of ice within the Astrolabe subglacial basin, Terre Adélie, East Antarctica: an hypothesis derived from numerical modelling experiments - Siegert, Martin J; Glasser, Neil F (Polar Research, 1997)
Keywords: Antarktis; geologi; geomorfologi; glasiologi; innlandsis; subglasial innsjø

Selvhevdelse og altruisme i Antarktis - Tamnes, Rolf (Oljealder : 1965-1995, 1997)
Keywords: Antarktis; Norge; utenrikspolitikk

Rondespiret - Tollefsen, Ivar; Sand, Vebjørn (Orion forl., 1997)
Keywords: Antarktis; Sydpolen; ekspedisjoner; fjellklatring; klatreekspedisjoner; malerkunst

Spatial and temporal variation of sublimation on Antarctica: Results of a high-resolution general circulation model - van den Broeke, Michiel R. (Journal of Geophysical Research: Atmospheres, 1997)
In this paper we use output of a high-resolution general circulation model (ECHAM-3 T106, resolution 1.1°?1.1°) to study the spatial and temporal variation of sublimation on Antarctica. First, we compare model results with available observations of sublimation rates. The yearly cycle, with small latent heat fluxes during the winter, is well reproduced, and the agreement with sparsely available spot observations is fair. The model results suggest that a significant 10?15% of the annual precipitation over Antarctica is lost through sublimation and that sublimation plays an important role in the formation of blue ice areas. A preliminary analysis of the atmospheric boundary layer moisture budget shows that the spatial variation of sublimation in the coastal zone of East Antarctica can be explained by variations of horizontal advection of dry air. Dry air advection, and thus surface sublimation, is enhanced in areas where katabatic winds are strong and have a large downslope component and where the Antarctic topography drops suddenly from the plateau to the coastal zone. In areas where horizontal advection is small, like the plateau and the large ice shelves, special conditions must be met to make significant sublimation at the surface possible.
Keywords: Antarktis; atmosfæren; geofysikk; meteorologi

Report of the Norwegian Antarctic Research Expedition 1996/97 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1997)
Keywords: Antarktis; NARE 1996/97; biologi; geodesi; geologi; glasiologi; oseanografi

Cold resistance and metabolic activity of lichens below 0°C - Kappen, Ludger; Schroeter, Burkhard; Scheidegger, Christoph; Sommerkorn, Martin; Hestmark, Geir (Proceedings of the F3.1, F3.4, F2.4 and F3.8 Symposia of COSPAR Scientific Commission F, 1996)
Laboratory measurements show that lichens are extremely tolerant of freezing stress and of low-temperature exposure. Metabolic activity recovered quickly after severe and extended cold treatment. Experimental results demonstrate also that CO2 exchange is already active at around −20°C. The psychrophilic character of polar lichen species is demonstrated by optimum temperatures for net photosynthesis between 0 and 15°C. In situ measurements show that lichens begin photosynthesizing below 0°C if the dry thalli receive fresh snow. The lowest temperature measured in active lichens was −17°C at a continental Antarctic site. The fine structure and the hydration state of photobiont and mycobiont cells were studied by low-temperature scanning electron microscopy (LTSEM) of frozen hydrated specimens. Water potentials of the frozen system are in the range of or even higher than those allowing dry lichens to start photosynthesis by water vapor uptake at +10°C. The great success of lichens in polar and high alpine regions gives evidence of their physiological adaptation to low temperatures. In general lichens are able to persist through glacial periods, but extended snow cover and glaciation are limiting factors.
Keywords: Antarktis; botanikk; frostresistens; lav; planter; polarområdene

Territoriell ekspansjonspolitikk - Fure, Odd-Bjørn (Mellomkrigstid : 1920-1940, 1996)
Keywords: Antarktis; Norge; historie; internasjonal; norske ekspedisjoner; polarområdene; politikk; utenrikspolitikk

Dagbok fra Sydpolen - Johansen, Hjalmar (Vågemot forl., 1996)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Anhydrobiosis and cold tolerance in tardigrades - Sømme, Lauritz (European Journal of Entomology, 1996)
A review of the literature regarding anhydrobiosis and cold tolerance in tardigrades is presented. During increasing desiccation, invertebrates like tardigrades, rotifers, nematodes and some collembolans are able to shut down metabolism to undetectable levels. When tardigrades are entering anhydrobiosis, a tun-like structure is formed, facilitated by structural adaptations of the cuticle. Slow dehydration is essential for tun formation, and the accumulation of trehalose during this process may help to stabilize phospholipids and proteins. Wax extrusion on the cuticle surface reduces transpiration. A fraction of 5-15% of the initial body water is retained during anhydrobiosis. Tardigrades are principally aquatic organisms, but anhydrobiosis makes it possible for some species to live in habitats with changing moisture conditions. Tardigrades in anhydrobiosis may tolerate exposure to freezing temperatures of liquid gases, and some species also survive such temperatures in their hydrated state. Few investigations are available on the relation of tardigrades to temperatures more representative to their natural environments. Experimental studies, however, from Greenland and the Antarctic Continent suggest that some species overwinter both in a hydrated frozen state and in anhydrobiosis. During the summer, a number of tardigrade species have been recorded from cryoconite holes, formed on the surface of glaciers. These species are freeze tolerant since their habitats are permanently frozen during the winter.
Keywords: Antarktis; Dronning Maud Land; biomonitorering; bjørnedyr; entomologi; kuldetoleranse; polarområdene; virvelløse dyr

Report of the Norwegian Antarctic Research Expedition 1993/94 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1996)
Keywords: Antarktis; NARE 1993/94; geodesi; glasiologi; ornitologi

Snille piker går ikke til Sydpolen - Arnesen, Liv (Damm, 1995)
Keywords: Antarktis; Sydpolen; ekspedisjoner; polarekspedisjoner; reiseskildringer

Norges polare interesser - Berg, Roald (Norge på egen hånd, 1995)
Keywords: Antarktis; Norge; historie; polarområdene; utenrikspolitikk

Using multiple data sources to enhance photogrammetry for mapping Antarctic terrain - Fox, Adrian J (Polar Research, 1995)
Keywords: Antarktis; flyfoto; geografi; kartlegging; luftfoto; satellittbilder

Cato mot Sydpolen - Hauge, Odd Harald; Bry, Knut; Ebbesen, Lars (Pax, 1995)
Keywords: Antarktis; Nordmenn; Sydpolen; ekspedisjoner; fotokunst; funksjonshemmede; oppdagelsesreiser; polarekspedisjoner; reiser; reiseskildringer

Immune responses during an antarctic summer - Lugg, Desmond J.; Ursin, Holger; Donovan, Kevin; Konrad Muller, H.; Quinn, Dennis (Pathology, 1995)
The immune status of 29 members of the Australian National Antarctic Research Expeditions (ANARE) was investigated before, during, and after a 56 day summer voyage to Antarctica and correlated with psychological and physiological parameters. All subjects were healthy. Expedition personnel demonstrated decreased cell mediated immune responses (CMI) assessed by the CMI Multi-test; 21% were hypoergic. The major associated observation was a significant negative correlation with anxiety in Antarctica. However, perceived anxiety was greater before and after the voyage. No significant changes were found in T and B lymphocyte subsets, immunoglobulin and complement components and cutaneous blood flow, nor was there any clinical evidence of illness. Of the hormones examined only cortisol was low predeparture which may reflect increased perceived anxiety at that time. Changes in immune control mechanism were apparent as shown by reduced CMI responses and lowered tetanus antibody levels. Stress factors are postulated to induce depression of the immune response in Antarctica. The association with anxiety suggests that brain peptides or associated cytokines may have a role in mediating these immune events. Such alterations in immune status have implications for health management in isolated and extreme conditions.
Keywords: Antarktis; fysiologi; immunologi; psykologi

Forskrift om vern av miljøet i Antarktis - Miljøverndepartementet (1995)
Keywords: Antarktis; jus; miljøvern

Polychlorinated Dibenzo-p-Dioxins, Dibenzofurans and Coplanar Biphenyls in Antarctic Fur Seal Blubber - Oehme, Michael; Schlabach, Martin; Boyd, Ian (Ambio, 1995)
Levels of polychlorinated dibenzo-p-dioxins (PCDD) and dibenzofurans (PCDF) as well as of coplanar (non-ortho substituted) polychlorinated biphenyls (CB-77, CB-126 and CB-169) have been determined in 11 fur-seal blubber samples from female Antarctic fur seals. Measurable PCDD/PCDF concentrations averaging 2 ppt TEQ (Nordic model) were found. This is considerably less than in Arctic seals. In addition, the PCDD/PCDF congener patterns differed between Antarctic and Arctic seals. The levels of CB-77, CB-126 and CB-169 (8.5-41 pg g-1 for single congeners in average) in Antarctic fur seals were also much lower than in Arctic ringed and harp seals. A possible explanation of these differences is the overall lower environmental pollution of the Southern Hemisphere, though an influence of different age and sex distributions cannot be excluded. The data passed all quality assurance criteria that had been established for such low levels.
Keywords: Antarktis; forurensning; marin biologi; miljøgifter; pinnipedier; polarområdene; seler

Invertebrates in Hot and Cold Arid Environments - Sømme, Lauritz (Springer-Verlag, 1995)
Keywords: Antarktis; forskning; kuldetoleranse; virvelløse dyr

Norske offentlige samlinger med kulturhistorisk polarmateriale - Barr, Susan (Norsk polarinstitutt, 1994)
Keywords: Antarktis; polarforskning; polarhistorie; polarområdene; polarsamlinger

Detailed studies of bottom freezing under an iceshelf and mapping of accumulation by use of multi-frequency pulse-aperture radar - Erlingsson, Bjørn; Gjessing, Yngvar; Hamran, Svein Erik; Holmlund, Per (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Antarktis; NARE 1991/92; ekspedisjoner; georadar; isshelf; topografi

Antarktis: verdens siste villmark - Fothergill, Alastair (Cappelen, 1994)
Keywords: Antarktis; Sørishavet; biologi; natur

Chemical fractionation of sea salt in snow - Gjessing, Yngvar; Erlingsson, Bjørn (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Antarktis; NARE 1991/92; kjemisk; sjøvann; snø

A model of ice shelf-ocean interaction with application to the Filchner-Ronne and Ross Ice Shelves - Nøst, Ole Anders; Foldvik, Arne (Journal of Geophysical Research: Oceans, 1994)
A simple analytical model has been developed to study the formation of Ice Shelf Water (ISW). ISW is assumed to flow as a buoyancy-driven layer underneath the ice shelf. A relation between potential temperature and salinity in the ISW layer is calculated from the mass and energy balance. This temperature-salinity relation is shown to depend only on the temperature and the salinity of the source water mass and to be practically independent of entrainment and melt rates. The model results are obtained without making any assumptions about entrainment and melt rates. The model is in good agreement with observations under the Ronne Ice Shelf, and it indicates that ISW in the Filchner Depression is formed from Western Shelf Water (WSW) with salinity higher than 34.75 practical salinity units. Such high-salinity water is only observed in the Ronne Depression in the western part of the continental shelf. This implies a circulation of WSW, under the Filchner-Ronne Ice Shelf, from the Ronne Depression into the Filchner Depression. Similarly, the model shows that the ISW observed under J9 at the Ross Ice Shelf has been formed from Low Salinity Shelf Water (LSSW) from the eastern parts of the Ross Sea continental shelf. LSSW must therefore circulate under the eastern parts of the Ross Ice Shelf.
Keywords: Antarktis; geofysikk; isshelf; kontinentalsokkel; oseanografi

Report of the Norwegian Antarctic Research Expedition 1991/1992 - Østerhus, Svein (ed.) (Norsk Polarinstitutt, 1994)
Keywords: Antarktis; NARE 1991/92; fugler; geologi; glasiologi; ornitologi; oseanografi

Rock mapping of glaciated areas by satellite image processing - Salvini, Francesco; Della Maggiore, Roberto; Fortunati, Luciano; Mazzarini, Francesco (Polar Research, 1994)
Keywords: Antarktis; geologi; polarområdene; satellitt bilder

Solorina Spongiosa in Antarctica: An Extremely Disjunct Bipolar Lichen - Smith, R. I. Lewis; Øvstedal, Dag Olav (The Lichenologist, 1994)
The bipolar foliose lichen Solorina spongiosa (Sm.) Anzi is reported from James Ross Island, Antarctica, where it grows on moss. This is only the third known occurrence of this lichen from the Southern Hemisphere, the other localities being in Tierra del Fuego and New Zealand. Its morphology resembles that of the New Zealand population and arctic-alpine populations from the Northern Hemisphere, although there are some differences in apothecial and spore size. As elsewhere, it occupies base-rich habitats colonized by predominantly calcicolous mosses and lichens.
Keywords: Antarktis; botanikk; lav; moser; planter

Proximal sub ice-shelf sedimentation Jutulgryta, East Antarctica - Solheim, Anders (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Antarktis; NARE 1991/92; glasiologi; isshelf

Geographical discoveries in Antarctica by the whaling industry - Headland, Robert Keith (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Antarktis; Carl Anton Larsen; Lars Christensen; ekspedisjoner; geografi; hvalfangst; oppdagelsesreiser

Dager i Antarktis: om folk og forskning, og en ekspedisjon litt utenom det vanlige - Kristensen, Monica (Grøndahl Dreyer, 1993)
Keywords: Antarktis; ekspedisjoner

Regulation of parental effort in a long-lived seabird an experimental manipulation of the cost of reproduction in the antarctic petrel, Thalassoica antarctica - Sæther, Bernt-Erik; Andersen, Reidar; Pedersen, Hans Christian (Behavioral Ecology and Sociobiology, 1993)
The fitness of a parent in an altricial bird species is likely to be a function of the proportion of resources allocated to offspring production in relation to the amount spent on its own survival. Here we report an experiment on the Antarctic petrel in which we manipulated the costs of rearing an offspring by placing small lead loads on the legs of one parent. The bird could then either decrease its own body reserves or reduce the food load to the chick. The manipulated birds decreased their food load and increased the feeding interval, compared with unmanipulated birds. Consequently, the rate of chick loss increased. No significant difference was found between the body weights of experimental and control birds during the experiment.
Keywords: Antarktis; fugler; ornitologi; petreller; zoologi; økologi

Søker fortiden og framtiden på Sydpolen - Bakka, Toril (Statoil magasin, 1992)
Keywords: Antarktis; biografi; ekspedisjoner

Atmospheric CO₂ and global warming: a critical review - Jaworowski, Zbigniew; Segalstad, Tom Victor; Hisdal, Vidar (Norsk Polarinstitutt, 1992)
Keywords: Antarktis; atmosfæren; drivhuseffekten; isbreer; karbondioksid; klimaendringer; klimagasser; paleoatmosfæren; temperaturforhold

Do glaciers tell a true atmospheric CO2 story? - Jaworowski, Zbigniew; Segalstad, Tom Victor; Ono, Nobuo (Science of The Total Environment, 1992)
Until 1985 most studies of CO2 in gas inclusions in pre-industrial ice indicated that CO2 concentrations (up to 2450 ppm) were higher than the current atmospheric level. After 1985, lower pre-industrial CO2 values were reported, and used as evidence for a recent man-made CO2 increase. The errors in these revised values, however, are of a similar magnitude to the apparent increase in atmospheric CO2 level. The assumptions used in estimating lower CO2 values in past atmospheres have been: no liquid phase in polar ice; younger age of air than of ice due to free gas exchange between deep firn and the atmosphere; and no change in composition of air inclusions. These assumptions are shown to be invalid. Liquid saline water exists in ice at low temperatures, even below −70°C; airtight ice layers are ubiquitous in Antarctic firn; and more than 20 physico-chemical processes operating in situ and in ice cores contribute to the alteration of the chemical composition of air inclusions. The permeable ice sheet with its capillary liquid network acts as a sieve which redistributes elements, isotopes, and micro-particles. Thirty-six to 100% of air recovered from old ice is contaminated by recent atmospheric air during field and laboratory operations. The value of ∼290 ppm, widely accepted from glacier studies for the pre-industrial atmospheric CO2 level, apparently results from: invalid assumptions; processes in ice sheets; artifacts in ice cores; and arbitrary rejection of high readings. To date, glaciological studies are not able to provide a reliable reconstruction of either the CO2 level in pre-industrial and ancient atmospheres or paleoclimates. Instead these studies have led to a widely accepted false dogma of man-made climatic warming. This dogma may have enormous negative impact on our common future.
Keywords: Antarktis; drivhuseffekt; glasiologi; global oppvarming; isbreer; karbondioksid; paleoklimatologi; stabile isotoper

Determination of sulphur- and chlorine-containing compounds using capillary gas chromatography and atomic emission detection - Pedersen-Bjergaard, Stig; Asp, Tone Normann; Greibrokk, Tyge (Analytica Chimica Acta, 1992)
The potential of universal calibration using capillary gas chromatography combined with atomic emission detection was evaluated for several chlorine- and sulphur-containing compounds of environmental interest. The elemental responses obtained for C, H, Cl and S were found to be affected by the molecular structure. Rapid determination of several analytes was accomplished using a single calibration graph based on one randomly selected reference compound, but 10–30% errors relative to the actual concentrations were observed in several instances. The results were significantly improved by using reference compounds with structures similar to those of the analytes of interest. the practical utility of universal calibration is illustrated by the determination of pesticides in stomach oil deposits from birds living in Antarctica.
Keywords: Antarktis; biokjemi; fugler; kjemi; kromatografi; petreller

Samtykke til ratifikasjon av Protokoll om miljøvern til Antarktistraktaten, undertegnet i Madrid 4. oktober 1991 - Utenriksdepartementet (1992)
Keywords: Antarktis; forvaltning; miljøvern; politikk

Vel blåst! Kommandør Chr. Christensens Hvalfangstmuseum gjennom 75 år 1917-1992 - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1992)
Keywords: Antarktis; Christen Christensen; Nordmenn; Vestfold; historie; hvalfangere; hvalfangstindustri; pelagisk; polarekspedisjoner

The ecophysiology of under-ice fauna - Aarset, Arne V (Polar Research, 1991)
Keywords: Antarktis; amfipoder; fauna; havis; polarområdene; sjøis; zoologi; økofysiologi

Foraging economics and performance of polar and subpolar Atlantic seabirds - Croxall, John P; Briggs, Dirk R (Polar Research, 1991)
Keywords: Antarktis; fugler; næring; ornitologi; pingviner; zoologi; økologi

Sydpolen på tvers - Høibakk, Ralph (Gyldendal, 1991)
Keywords: Antarktis; Den Norske Sydpolekspedisjonen 1990; Sydpolen; ekspedisjoner; reiser; reiseskildringer

Occurrence of polar seabirds at sea in relation to prey concentrations and oceanographic factors - Hunt Jr, George L (Polar Research, 1991)
Keywords: Antarktis; næring; ornitologi; oseanografi; polarområdene; sjøfugler; økosystemer

The lichen genus Stereocaulon in Antarctica and South Georgia - Smith, Ronald I Lewis; Øvstedal, Dag Olav (Polar Biology, 1991)
Six species of Stereocaulon and one unnamed taxon (close to S. glabrum) are reported from South Georgia, the maritime Antarctic islands and Antarctic Peninsula. S. caespitosum is new to the western sub-Antarctic. Variations in morphology and secondary chemistry are provided, and the ecology and geographical distribution in the sub-Antarctic and Antarctic biomes are given for each taxon.
Keywords: Antarktis; botanikk; lav; planter

Psychobiological Studies of Individuals in Small, Isolated Groups in the Antarctic and in Space Analogues - Ursin, Holger; Bergan, Tom; Collet, Jérôme; Endresen, Inger M.; Lugg, Desmond; Maki, Pauline; Matre, Roald; Molvær, Otto Inge; Müller, Helmut K.; Olff, Miranda; Pettersen, Roger C.; Sandal, Gro Mjeldheim; et al. (Environment and Behavior, 1991)
Mental and physical health are both at risk under conditions of prolonged remoteness from home and removal from normal social support networks. This article examines relevant data from small groups isolated in (a) Antarctic summer stations, (b) a Transantarctic traverse expedition, and (c) a spacecraft simulator capsule.
Keywords: Antarktis; forskningsstasjoner; fysiologi; immunologi; psykobiologi; psykologi

Sandefjord - et naturlig polarforskningssenter - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1991)
Keywords: Antarktis; Norsk Polarinstitutt; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Predatory feeding behavior of an Antarctic marine copepod, Euchaeta antarctica - Yen, Jeannette (Polar Research, 1991)
Keywords: Antarktis; fytoplankton; hoppekreps; marin biologi

The pelagic distribution of marine birds in a heterogeneous environment - Hunt Jr, George L. (Polar Research, 1990)
Keywords: Antarktis; fugler; marin ornitologi; næring; polarområdene

The pelagic distribution of marine birds in a heterogeneous environment - Hunt Jr, George L (Polar Research, 1990)
Keywords: Antarktis; fugler; ornitologi; polarområdene; zoologi

I hjertet av Antarktis; Norge i Antarktis - Imbert, Bertrand C; Hem, Arne (Polarforskningens pionerer, 1990)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; hvalfangst; oppdagelsesreiser

Virkninger av klimaendringer i polarområdene : bidrag til den interdepartementale klimautredningen - Kverndal, Arnt-Ivar; Elvebakk, Arve; Jaworowski, Zbygniew; Hansson, Rasmus (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; biologi; drivhuseffekten; dyreliv; fiskeri; flora; havbruksnæring; havis; havnivå; isbreer; klimaendringer; klimagasser; permafrost; planter; polarområdene; vannressurser; økologi

Some Nitzschia and related diatom species from fast ice samples in the Arctic and Antarctic - Medlin, Linda K.; Hasle, Grethe Rytter (Polar Biology, 1990)
Some Nitzschia and closely related species have been examined in the light and electron microscopes from fast ice samples in the Arctic and Antarctic. Nitzschia neofrigida, forming arborescent colonies, and Nitzschia promare, forming loose ribbon colonies, are described as new species, both probably included in the distribution of other similar species. A new combination, Auricula compacta, represents the first report of this genus from ice samples. Colony formation is reported for the first time in Nitzschia arctica and Nitzschia taeniiformis. No biopolar species were found and several reports of Arctic species in Antarctic ice samples have been refuted.
Keywords: Antarktis; alger; biodiversitet; biologi; botanikk; diatomeer; fytoplankton; planteplankton; polarområdene

Report of the Norwegian Antarctic Research Expedition 1989/90 - Norsk, Polarinstitutt (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; Dronning Maud Land; NARE 1989/90; Troll forskningsstasjon; Weddellhavet; geologi; marin økologi; meteorologi; zoologi

Frimerkespalten - Tandberg, Arne Ingar (Skipet, 1990)
Keywords: Antarktis; Bouvetøya; ekspedisjoner; filateli; historie; logistikk; skip